Asia-Pacific geopolitics hegemony vs. human security - Camilleri, Joseph A. 1944-; Marshall, Larry; Michael, Michális S.; Seigel, Michael T. (Edward Elgar, 2007)
This book brings together distinguished scholars and experts on public policy, social ethics, defence, human security and sustainability to consider the future of the Asia-Pacific region and appropriate responses by both states and civil society. It will appeal to scholars and researchers of international relations, politics and Asian studies as well as policymakers in the region.